Justification of the parameters of the active conical wood deformer - Padalka, Viacheslav; Gorbenko, Oleksandr; Ivankova, Olena; Dudnyk, Volodymyr; Horiunov, Bohdan (Technology audit and production reserves, 2025)
The object of research is the parameters of mechanisms for the destruction of anisotropic materials by a conical mechanical deformer. One of the known renewable energy sources is a material of plant origin (wood). Based on this, the search for optimal operating parameters and design features of working bodies for mechanized splitting of logs is relevant. Therefore, a new solution to the scientific problem is proposed, which consists in substantiating the main geometric parameters of an active conical deformer for splitting logs from wood at the lowest energy costs for its drive. The analysis conducted during the study showed a general positive feature of the principle of operation, in which the penetration of an active deformer of a conical shape perpendicular to wood fibers facilitates the destruction of their ties and has a more promising and productive design. A mathematical model for determining the force required to destroy a log of wood has been developed. The specified dependence takes into account the elastic characteristics of the material, the forces that exist between the fibers of anisotropic substance, the friction forces between the deformer material and wood, and its geometric parameters. It was determined that the necessary value that characterizes the physical and mechanical properties of wood is the force required to destroy the bonds between the fibers (coefficient of longitudinal destruction). Therefore, the values of the coefficient of longitudinal destruction were experimentally obtained, which were for pine – 2533 ± 66 N/m, oak – 5583 ± 145 N/m and aspen – 5000 ± 279 N/m. According to the research results, analytical recommendations for the geometric parameters of the active deformer were obtained. For pine material with a diameter of 0.15 m, the optimal cone length is in the range of 0.02–0.20 m at a cone angle of 20–90°. At the same time, the theoretical force for its destruction is 568–864 N. Similar results were also obtained for aspen and oak materials. This provides the opportunity to design the design of a conical wood deformer according to the specified ranges, which are optimal for each material or their groups.